Ecuador : First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Quantitative Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Ecuador. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
On September 30, 2020, the IMF Executive Board approved a 27-month arrangement under the Extended Fund Facility (EFF) with exceptional access (SDR 4,615 million, 661 percent of quota, about USD 6.5 billion) to help Ecuador restore macroeconomic stability and pursue the unfinished structural agenda from the previous program. High frequency indicators point to improvements in economic activity after bottoming out in Q2, while oil prices have been declining relative to earlier assumptions, leaving the macroeconomic outlook broadly unchanged over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet